Policy Impact dalam Penyusunan APBDes terhadap Realisasi Implementasi Anggaran di Desa Plumbon, Kecamatan Indramayu - Ibrahim Ibrahim; Sihabudin Sihabudin (Lembaga Pengembangan Kinerja Dosen, 2024)
The preparation of the Village Budget is carried out by involving the community through village deliberations. After being approved by the village deliberation, the Village Budget is then submitted to the Village Consultative Body (BPD) to be stipulated as a village regulation. After being enacted, the Village Budget can be used as a reference in implementing development activities and public services in the village. This research is a type of qualitative research with the aim of finding out evidence related to the preparation of the village budget and income whether or not it is in accordance with Village Regulation No. 9 of 2022 concerning the Village Revenue and Expenditure Budget. This type of research method is descriptive with a qualitative approach. The results of this study indicate that the preparation of the Village Budget and the implementation of the Village Budget are in accordance with Village Regulation No. 9 of 2022.